2013
DOI: 10.12942/lrsp-2013-4
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and Prediction of Variations in the Open Solar Magnetic Flux and Interplanetary Conditions

Abstract: Historic geomagnetic activity observations have been used to reveal centennial variations in the open solar flux and the near-Earth heliospheric conditions (the interplanetary magnetic field and the solar wind speed). The various methods are in very good agreement for the past 135 years when there were sufficient reliable magnetic observatories in operation to eliminate problems due to site-specific errors and calibration drifts. This review underlines the physical principles that allow these reconstructions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
173
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(185 citation statements)
references
References 234 publications
(318 reference statements)
9
173
0
1
Order By: Relevance
“…The coronal holes are the sources of (mainly weakly magnetic) solar winds and this generates the conclusion that the solar wind must be strong and mainly with a low magnetic flux in (the) coming cycle(s). This has indeed been observed (Lockwood et al 2009, Lockwood 2013, and that finding is a fine confirmation of the Makarov-TlatovCallebaut observations. This phenomenon may, perhaps only partly, be related to the latitude drift of sunspots (Richardson and Schwarzschild 1953;Tuominen 1954): at latitudes below 26 • the spots move equatorward, the faster when closer to the equator, with an extreme value of 0.017 degrees per day at 2 • latitude.…”
Section: Unipolar Magnetic Regions; Their Significance For Solar Varisupporting
confidence: 84%
See 2 more Smart Citations
“…The coronal holes are the sources of (mainly weakly magnetic) solar winds and this generates the conclusion that the solar wind must be strong and mainly with a low magnetic flux in (the) coming cycle(s). This has indeed been observed (Lockwood et al 2009, Lockwood 2013, and that finding is a fine confirmation of the Makarov-TlatovCallebaut observations. This phenomenon may, perhaps only partly, be related to the latitude drift of sunspots (Richardson and Schwarzschild 1953;Tuominen 1954): at latitudes below 26 • the spots move equatorward, the faster when closer to the equator, with an extreme value of 0.017 degrees per day at 2 • latitude.…”
Section: Unipolar Magnetic Regions; Their Significance For Solar Varisupporting
confidence: 84%
“…An important feature is the coronal holes. These are non-magnetic regions or at best regions with a small magnetic field that are mainly situated in polar areas but that do sometimes extend down to fairly low latitudes as already mentioned in the preceding Section (Zwaan 1987;Makarov et al 2004;Lockwood et al 2009;Lockwood 2013). The behavior of the polar and equatorial activity during and prior to the phase transition is shown in Fig.…”
Section: Polar Variability In the Framework Of The Total Solar Variationmentioning
confidence: 82%
See 1 more Smart Citation
“…Ganushkina et al (2015) described the observed morphology of the current systems and the measurements used to characterise them. Lockwood (2013) provided an overview of the current systems and the geomagnetic indices which are used to monitor their intensity and variability, with the aim of determining changes in interplanetary conditions over the last dozen or so solar cycles (150 years or more). Also of interest to this topic is the review of which describes our present understanding of solar wind-magnetosphere-ionosphere coupling, that is the dynamics of the magnetosphere in response to solar wind driving, which in turn are responsible for many of the current systems within the magnetosphere.…”
mentioning
confidence: 99%
“…We note that this is somewhat shorter than the corresponding ∼ 60 min long phases of field stretching before dipolarizations observed during the conditions of continuously high (3-4 nPa) dynamic pressure in the case of the sawtooth substorms on 18 August 2003 . Concerning the mechanism for the relation between solar wind dynamic pressure and the stretching of the magnetic field in the nearEarth PS, we refer to Karlsson et al (2000) and Lockwood (2013).…”
Section: Discussionmentioning
confidence: 99%